Analysis of Challenges Facing Post-Basic Education and Career Development (PBECD) in Nigeria and Way Forward - Ogunode Niyi Jacob; Mary Mamman Sawa (Researchparks Publishing, 2022)
This paper examined the challenges facing Post-Basic Education and Career Development (PBECD) in Nigeria. Secondary data were used in the paper. The paper identified inadequate funding, inadequate infrastructural facilities, inadequate professional teachers, corruption, insecurity problems, poor supervision, poor quality assurance, weak school administrators, prevalence of examination malpractice, over-population, poor capacity building, poor implementation of Post-Basic Education and Career Development (PBECD) policies and ineffective guidance and counselling programme as challenges facing Post-Basic Education and Career Development (PBECD) in Nigeria. The paper recommended that government should increase the funding of Post-Basic Education and Career Development (PBECD) in Nigeria.